Screen time and myopia: A serial multiple mediator SEM analysis - Xie, Jinchen; Lu, Chuntian; Zhu, Jie (Frontiers in Public Health, 2022)
Background: The COVID-19 has affected education systems worldwide, making digital devices common arrangements for college students, whether leisure or information. In China, ninety percent of college students suffer from myopia. Excessive screen use alters college students’ lifestyles, implies potential health risks, and affects opportunities to jobs. It is important to reveal the underlying mechanisms between screen time use and myopia among college students. Methods: This paper evaluate the characteristics of myopia of 759 college students from Seven randomly selected universities in mainland China from Sep 13 to Dec 12, 2021, and set a multiple-mediator SEM model to analysis the potential mechanism of screen time and myopia. Results: We obtain three valuable conclusions as fellow. Firstly, there is no significant direct relationship between screen time and myopia among Chinese college students during the COVID-19. Secondly, sedentary behavior and physical activity significantly predicted the increase/decrease of myopia among Chinese college students, respectively. Thirdly, a serial multiple-mediator that encompassed sedentary behavior and physical activity sequentially completely mediated the relationship between screen time and myopia. Conclusions: Although there was no directly-significant relation between screen time and myopia, screen time can significantly affect the risk of myopia indirectly by influencing sedentary behavior and physical activity. Our study demonstrates the need to prevent the potential effects of overuse of electronic devices on myopia in college students, especially during the COVID-19.